Kilconnell Franciscan Friary, exterior south transept, west window, mullion - O'Donovan, Danielle (My University, 2009)
Mullion of finely moulded window in south transept. The mullion is moulded at its outer face and simply has chamfered corners at the rear. The moulding, from centre comprises: central fillet flanked at either side by hollow chamfer, right-angled rebate, hollow.
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Tracery (Architecture); Late Medieval; moldings, hollow; mullions; fillets (moldings)